Hospital-Acquired Infections: Challenges, Causes, and Prevention Strategies in Healthcare - Oliveira da Costa, Marise; Carvalho Deus, Gláucia; Lopes Orfão, Andréa; Barreto, Moacyr Starich Guerra; Mourão, Felipe Areias; Rodrigues, Eluananda Borges; Moreira, Sabrina Ferreira (Brazilian Journal of Implantology and Health Sciences, 2025)
Hospital-acquired infections represent one of the greatest challenges to patient safety and the quality of healthcare due to their direct association with increased morbidity and mortality, longer hospital stays, and higher healthcare costs. This study aims to identify, through a literature review, the main challenges, causes, and prevention strategies for hospital-acquired infections in the contemporary hospital setting. The adopted methodology was an integrative literature review, with a search conducted in the Virtual Health Library - VHL using controlled descriptors combined with Boolean operators. Articles included were those available in full, focusing on the clinical, organizational, and strategic aspects of hospital infections. At the end of the screening and analysis process, nine studies comprised the final sample. Results indicated that the main challenges related to hospital-acquired infections include failures in hand hygiene, inappropriate use of antimicrobials, improper management of invasive devices, and lack of adherence to institutional protocols. Effective prevention strategies include continuous staff training, implementation of disinfection routines, rational use of antibiotics, and active surveillance by hospital infection control committees. The role of the intensive care nurse, clinical pharmacist, and nursing staff is also highlighted as key elements in mitigating risks. The study concludes that, although the challenges of hospital-acquired infections are widely recognized, the gap between theory and practice remains significant. Effective prevention requires interdisciplinary actions, ongoing education, continuous surveillance, and institutional engagement. Investing in applied research and more robust methodologies may strengthen the evidence base and guide best practices in addressing hospital-acquired infections.